CrystalExplorer model energies and energy frameworks: extension to metal coordination compounds, organic salts, solvates and open-shell systems. (2017) - Mackenzie, Campbell F.; Spackman, Peter R.; Jayatilaka, Dylan; Spackman, Mark A.
No abstract available